Reply to Futures regarding Diesendorf response to Floyd et al., "Energy descent as a post-carbon transition scenario: How 'knowledge humility' reshapes energy futures for post-normal times", 2020. (June 2022) - Floyd, Joshua; Alexander, Samuel; Palmer, Graham; Moriarty, Patrick
Abstract: Floyd et al. (2020), 'Energy descent as a post-carbon transition scenario: How 'knowledge humility' reshapes energy futures for post-normal times', addresses anticipatory challenges associated with the envisaged transition from fossil fuels to renewable energy. We make the case that the epistemic nature of analytical techniques based on quantitative modelling is such that they cannot establish in any definitive sense the feasibility of providing present and future projected global energy services via renewable sources, and that as such energy transition governance and management approaches should be adopted that recognise and respond to this situation, including the plausibility of futures characterised by energy descent that it implies. A response from Mark Diesendorf mischaracterises our case in multiple ways, including to suggest that it is an argument against renewable energy. Further, the response fails to engage with the substance of our arguments for the plausibility of energy descent, and in multiple instances presents our arguments erroneously. We identify the specific failings of the response and show why its claim to have refuted our case is not supported. We discuss the broader implications of the epistemic stance on which the response is based for energy-society futures inquiry. Highlights: A reply to 'Energy descent as a post-carbon transition scenario: How 'knowledge humility' reshapes energy futures for post-normal times' mischaracterises our case. In addition, the reply fails to engage with the substance of our arguments, and in multiple instances presents our arguments erroneously. We identify the specific failings of the response and show why its claim to have refuted our case is not supported. We discuss the broader implications of the epistemic stance on which the response is based for energy-society futures enquiry.